(1)H NMR-linked metabolomics analysis of liver from a mouse model of NP-C1 disease - Ruiz-Rodado, V; Nicoli, E; Probert, F; Smith, D; Morris, L; Wassif, C; Platt, F; Grootveld, M (American Chemical Society, 2016)
Clinical manifestations of Niemann-Pick type C1 (NP-C1) disease include neonatal hepatosplenomegaly and in some patients progressive liver dysfunction and failure. This study involved a (1)H NMR-linked metabolomics analysis of liver samples collected from a NP-C1 disease mutant mouse model in order to explore time-dependent imbalances in metabolic pathways associated with NP-C1 liver dysfunction, including fibrosis. NP-C1 mutant (Npc1(-/-); NP-C1), control (Npc1(+/+); WT), and NP-C1 heterozygous mice (Npc1(+/-); HET) were generated from heterozygote matings. Aqueous extracts of these liver samples collected at time points of 3, 6, 9, and 11 weeks were subjected to high-resolution NMR analysis, and multivariate (MV) metabolomics analyses of data sets acquired were performed. A MV random forests (RFs) model effectively discriminated between NP-C1 and a combined WT/HET hepatic NMR profiles with very high predictive accuracy and reliability. Key distinguishing features included significant upregulations in the hepatic concentrations of phenylalanine, tyrosine, glutamate, lysine/ornithine, valine, threonine, and hypotaurine/methionine, and diminished levels of nicotinate/niacinamide, inosine, phosphoenolpyruvate, and 3-hydroxyphenylacetate. Quantitative pathway topological analysis confirmed that imbalances in tyrosine biosynthesis, and hepatic phenylalanine, tyrosine, glutamate/glutamine, and nicotinate/niacinamide metabolism were involved in the pathogenesis of NP-C1 disease-associated liver dysfunction/damage. (1)H NMR-linked metabolomics analysis provides valuable biomarker information regarding hepatic dysfunction or damage in NP-C1 disease.